منوّر صمادح و "صوت الشابي من وراء العدم" قراءةٌ نقديَّة في القصيدة - مردف, سعد (جامعة الوادي - university of Eloued, 2022)
هذه سياحَةٌ نقديَّة في زاوية منْ زَوايا الكون الشعري للشاعر التونسي منوّر صمادح، تحتَ ظلال قصيدتِه (صوت الشابي من وراء العدم)، حمَلتْ قراءةً في متنِها النصِّي، واستجلاءً لأهمِّ خصائصِه الأسلوبية لغة، و إيقاعًا، و تخييلا، ورؤية، وانطوتْ كذلكَ على نظرة في نزعته الوجدانية، وطريقتِه في اعتمادِ المعادل الموضوعيِّ لتجربته الذاتية من خلال افتراضِ مُرسَلةٍ شعرية من السماء تحملُ موقفَهُ، واستشرافَهُ، ورغباتهِ، وآمالَه التي ركَزَهَا في شخص رفيقهِ أبي القاسم الشابي، وبعَثَها نصَّا شعريَّا طافحًا بالشكوى، والُحلم، وإعلان البراءة من عالمِ التراب، والنكْرانِ. عالمِ التراب، والنكْرانِ. This is a critical tourism in a corner of the poetic universe of the Tunisian poet Mnaouar Samadah, through his poem (The Voice of Chebbi from Behind Nothingness), which carried a reading in its content, and an explanation of its most important stylistic characteristics language, rhythm, imagine, vision, and also involved a look at the removal of His emotional attitude, his way of adopting the objective equivalent of his own experience by assuming a poetic message from heaven that carries his position, his foresight, his desires, his hopes that he focused on the person of his companion Abu Qasim Chebbi, and sent her a poetic text full of complaints, Dream, declaration of innocence from the world of dirt, denial. Keywords: Poetic dictionary. Musical effect. Whisper. Poetic language. Imagination. Romanticism.
مقال
Keywords: كلمات مفتاحية/ المعجم الشعري. الأثر الموسيقي. الهمس. اللغة الشعرية. التخييل. النزعة الرومانسية.